Using Nonheparin Anticoagulant to Treat a Near-Fatal Case With Multiple Venous Thrombotic Lesions During ChAdOx1 nCoV-19 Vaccination-Related Vaccine-Induced Immune Thrombotic Thrombocytopenia. Issue 9 (2nd June 2021) - Bersinger, Samuel; Lagarde, Kevin; Marlu, Raphael; Pernod, Gilles; Payen, Jean-Francois
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe the successful recovery from multiple and life-threatening venous thrombosis after ChAdOx1 nCoV-19 vaccination. DESIGN: Case report. SETTING: University Hospital. Patient: Few days after the first dose of the ChAdOx1 nCoV-19 vaccine, a 21-year-old woman experienced massive thrombosis in the deep and superficial cerebral veins together with seizures, neurologic focal deficit, and thrombocytopenia. In the neurointensive care unit, her condition worsened despite early decompressive craniectomy. She developed bilateral segmental pulmonary embolism, left hepatic, and left external iliac venous thrombosis. INTERVENTION: Argatroban (0.5–2.2 µg/kg/min) and high-dose IV immunoglobulin (1 g/kg/d for 2 consecutive days) were initiated on day 6 after admission. With these therapies, there was a gradual resolution of multiple sites of venous thrombosis, and platelet count returned to normal. The patient left the ICU with full consciousness, expressive aphasia, and right hemiparesis. CONCLUSIONS: This case of vaccine-induced immune thrombotic thrombocytopenia shows that a good outcome can be obtained even with multiple and life-threatening venous thrombotic lesions. Argatroban and high-dose IV immunoglobulin along with management of severe cerebral venous thrombosis played a major role in this epilogue.